Allelopathic effects of Eucalyptus camaldulensis and Eucalyptus globules leaf extracts mixture on Germination and Growth of Sorghum - D.M.,, Musyimi; P.A, Sikuku; G., Opande; Vicky, Korir (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Allelopathy results when living organisms produce bioactive compounds which enter the environment and produce direct or indirect effects on the growth and development of the same or other species. Many investigations have been carried out on allelopathic effect of Eucalyptus leaf extracts on several cereals. E. camaldulensis and E. globulus contain allelochemicals that inhibit growth of agricultural crops. This study was done to investigate the allelopathic effect ofa mixture of E. camaldulensis and E. globules on germination and growth of Sorghum bicolor. The seeds of Sorghum bicolor were germinated in sterilized petri dishes lined with a layer of filter paper Whatman No.1, soaked daily withtap water(control) and four different concentrations (25%, 50%, 75% and 100%) of fresh leaf extract mixture of E. camaldulensis and E. globulus in Department of Botany laboratory of Maseno University. Growth tests were carried out in the greenhouse using 4.5l plastic pots. Five plastic pots were half filled with top humus soil and different amounts of E. camaldulensis and E. globulus leaf segments mixture incorporated (0, g, 50g, 100g, 150g and 200g). The treatments were replicated five times and laid in completely randomized design. Data on seeds germinating, coleoptile and radicle length, plant shoot height, leaf length and width, leaf area and number of leaves was recorded. Data obtained was subjected to analysis of variance (ANOVA). Treatments means were compared using Least Significant Difference (LSD) at (p≤ 0.05).The fresh leaf aqueous extract mixture ofE. camaldulensis and E. globules significantly reduced germination of seeds, coleoptile and radicle lengthof S. bicolor.The fresh leaf segments mixture of E. globulus and E. camaldulensis incorporated to soil significantly reduced shoot height, leaf area, fresh weight and dry weight and chlorophyll content of S. bicolor.The study indicated that fresh aqueous leaf extract mixture and leaf segments of E. camaldulensis and E. globules have inhibitory effect on S. bicolor